Transformasi Makna Mezbah : Dari Tradisi Ibrani ke Kehidupan Spiritual Modern - Andra Andra; Roni Listen Saerejen; Malik Bambangan (Pusat Riset dan Inovasi Nasional, 2025)
This article discusses the transformation of the meaning of the altar from Hebrew tradition to modern spiritual life, highlighting the important role of the altar as a symbol of the relationship between humans and God. In Hebrew tradition, the altar serves as a physical altar for offering sacrifices, reflecting the sacrifice, purification, and spiritual commitment of the people of Israel. However, as time has progressed, the meaning of the altar has evolved into a deeper symbol that encompasses spiritual and emotional aspects. In a modern context, the altar is interpreted as a symbol of the human heart, a place where worship and devotion to God are performed wholeheartedly. This article also explores the application of altar values, such as devotion, humility, and service, in everyday life. Additionally, the concept of the altar is connected to universal interpretations that are relevant to various spiritual traditions. The method used in this research is a qualitative method with a literature study approach, involving the collection and analysis of literature and biblical verses related to the altar. Thus, this article aims to provide a deep understanding of the essence of the altar as a spiritual element that remains relevant, universal, and applicable in daily life, while inviting readers to reflect on the application of the altar concept in their lives.